Non-invasive treatment with near-infrared light: A novel mechanisms-based strategy that evokes sustained reduction in brain injury after stroke. Issue 4 (April 2020) - Strubakos, Christos D; Malik, Michelle; Wider, Joseph M; Lee, Icksoo; Reynolds, Christian A; Mitsias, Panayiotis; Przyklenk, Karin; Hüttemann, Maik; Sanderson, Thomas H
Ischemic stroke is a debilitating disease that causes significant brain injury. While restoration of blood flow is critical to salvage the ischemic brain, reperfusion can exacerbate damage by inducing generation of reactive oxygen species (ROS). Recent studies by our group found that non-invasive mitochondrial modulation with near-infrared (NIR) light limits ROS generation following global brain ischemia. NIR interacts with cytochrome c oxidase (COX) to transiently reduce COX activity, attenuate mitochondrial membrane potential hyperpolarization, and thus reduce ROS production. We evaluated a specific combination of COX-inhibitory NIR (750 nm and 950 nm) in a rat stroke model with longitudinal analysis of brain injury using magnetic resonance imaging. Treatment with NIR for 2 h resulted in a 21% reduction in brain injury at 24 h of reperfusion measured by diffusion-weighted imaging (DWI) and a 25% reduction in infarct volume measured by T2-weighted imaging (T2WI) at 7 and 14 days of reperfusion, respectively. Additionally, extended treatment reduced brain injury in the acute phase of brain injury, and 7 and 14 days of reperfusion, demonstrating a >50% reduction in infarction. Our data suggest that mitochondrial modulation with NIR attenuates ischemia–reperfusion injury and evokes a sustained reduction in infarct volume following ischemic stroke.